2009
DOI: 10.1200/jco.2008.16.8351
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum HER2 Extracellular Domain Assessment in Clinical Decision Making: Pooled Analysis of Four Trials of Trastuzumab in Metastatic Breast Cancer

Abstract: Based on our data, we cannot recommend using serum HER2 ECD levels to make trastuzumab or other treatment decisions for individual patients with advanced/metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 35 publications
4
83
0
7
Order By: Relevance
“…Many other membrane-anchored proteins release their ECD through proteolytic cleavage, such as HER2 and EGFR (28,29). However, clinical significance of such form has been difficult to establish, and effect on response to targeted therapy has not been fully elucidated (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Many other membrane-anchored proteins release their ECD through proteolytic cleavage, such as HER2 and EGFR (28,29). However, clinical significance of such form has been difficult to establish, and effect on response to targeted therapy has not been fully elucidated (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Serum HER2 is the circulating HER2 ECD shed from the surface of tumor cells, and thus it could be used as a diagnostic marker for tissue HER2 status. Numerous studies have investigated the clinical utility of serum HER2 analysis in breast cancer and recent reviews concluded that there is insufficient evidence to support the use of serum HER2 in the clinical management of breast cancer patients [13][14][15]. In contrast, only a small number of retrospective studies have investigated serum HER2 in gastric cancer to date and its clinical significance has not been determined.…”
mentioning
confidence: 99%
“…In patients with breast carcinoma, the overexpression of HER2 is an important predictor for the response of trastuzumab (11). In this study, lung ACs had a significantly higher rate of HER2 IHC staining than LCNEC, with only 2 LCNEC cases showing overexpression of HER2.…”
Section: Discussionmentioning
confidence: 49%
“…Overexpression of the human epidermal growth factor receptor 2 (HER2) tyrosine kinase, usually due to over-amplification, has been linked to poor prognosis in breast cancer (11). Treatment with recombinant monoclonal anti-HER2 antibody (trastuzumab) displays activity in patients with breast cancer, particularly with high HER2 expression.…”
Section: Introductionmentioning
confidence: 99%